Studi Komparasi Antara Strategi Mind Mapping Dengan Teams Games Tournament (TGT)Terhadap Hasil Belajar IPS Siswa Kelas III SDIT Nur Hidayah Surakarta Tahun Ajaran 2015/2016 - Qonita'ah Purwaningrum, Selvameidha; , Drs. Saring Marsudi, SH. M.Pd (2016)
This study aims to determine 1) the difference in student learning outcomes in the strategic use of Mind Mapping Strategies Teams Games Tournament (TGT) in Class III SDIT Nur Hidayah Surakarta, 2) Knowing which one is better, the learning outcomes of students who apply learning strategy Mind Mapping compared to implementing learning strategies Teams Games Tournament (TGT) in social studies students of class III SDIT Nur Hidayah Surakarta. This type of research is quantitative research experiment. Subjects of this study third grade students of class III C and D in SDIT Nur Hidayah Surakarta in 2015/2016. The data collection technique using the techniques of tests and documentation. Use traditional data analysis techniques t test which are preceded by the prerequisite test analysis, the homogeneity test and test for normality. Based on the results of data analysis with significance level of 5% obtained t> t table is 2,789> 1,994 with the average value of learning outcomes Class III C is greater than the third class D SDIT Nur Hidayah Surakarta, ie 83.75> 81.667. The conclusion of this study are as follows: 1) There are differences in learning outcomes Social Sciences (IPS) students taught using Mind Mapping Strategies and Strategy Teams Games Tournament (TGT) class III SDIT Nur Hidayah Surakarta Academic Year 2015/2016 2) Application Mind Mapping strategies in class III C is better than the implementation of the strategy Teams Games Tournament (TGT) in class III D class III SDIT Nur Hidayah Surakarta Academic Year 2015/2016.